Eat more, weigh less : Dr. Dean Ornish's life choice program for losing weight safely while eating abundantly - Ornish, Dean. (New York : HarperCollins, 1993)
Contains the author's Life Choice program that is based on the type of food consumed rather than the amount, and includes 250 low fat recipes.
Includes bibliographical references (p. 405-406) and indexes.
Library Journal
New York Times
Wilson's Public Library
Young Adult
Young Adult
Keywords: Low-fat diet; Low-fat diet -- Recipes; Reducing diets; Weight loss